Ecological Assessment of Animal World of South Usturt National Park (Texas Journal of Agriculture and Biological Sciences, 2023)
This article includes the results of zoological research conducted in South Ustyurt National Nature Park in 2021. From zoological and ecological methods generally accepted in scientific research (Formozov, 1952; Novikov, 1953; Smirnov, 1964; William, 2006). Scientific research work was carried out in the spring, summer, autumn and winter seasons of 2021 in the territory of the South Ustyurt National Nature Park.